Anion selectivity properties of ruthenium(II) tris(5,5 '-diamide-2,2 '-bipyridine) receptors dictated by solvent and amide substituent - Uppadine, L; Drew, M; Beer, P (2001)
The ratio of the dichloromethane-methanol solvent mixture medium and nature of the receptor amide substituent critically dictates chloride vs. nitrate selectivity properties of new ruthenium(II) tris(5,5′-diamide-2,2′-bipyridine) receptors.